Exploring Professional Identity Development in Medical Laboratory Professional Students ... - Hardy, Gregory Scott (Werklund School of Education, 2020)
Despite being the fourth largest health profession in Canada, medical laboratory science is perhaps one of the most poorly studied and underrepresented health care fields. While substantial research exists surrounding more well-known health care professions like nursing and medicine, there has been a minimal exploration of the sociological, cultural, and educational aspects of the medical laboratory profession in Canada. Given educational programs and clinical experiences are central to professional socialization processes and professional identity formation in health care professions, this research explores this process in a cohort of medical laboratory science students in the province of Newfoundland and Labrador, Canada. Drawing from a conceptualization of professional identity development as a form of learning shaped through cognitive, emotional, and social dimensions of lived experience, I explored the individual and professional experiences of students in a contemporary medical laboratory training ...